A high-efficiency full-wave CMOS rectifying charge pump for RF energy harvesting applications. Issue 12 (December 2015) - Wang, Weiyin; Wong, Hei; Han, Yan
Abstract: A high-efficiency integrated full-wave CMOS rectifying charge pump for radio-frequency (RF) energy harvesting was designed. By using the commercially available 40 nm CMOS process, low-voltage operation as low as 0.4 V was achieved by adopting body-connected PMOS diodes as the rectifying diodes and as switches for capacitor charging pump. A full-wave rectifying configuration was used to enhance the power conversion efficiency (PCE) of the converter. Simulation results indicate that the circuit can achieve a power efficiency of over 50.0% for an input voltage larger than 0.4 V of a single narrow band 900 MHz RF signal. Although the loading characteristics of the primitive charge pump, especially for 0.4 V input which is just above the specific threshold voltage of the PMOS, is rather poor, and a large voltage drop due to the conduction loss was found when the load current increases, it may still be acceptable for battery charging applications. A regulation circuit based on the charge pump switching control was then proposed to improve the loading characteristics.